Add-on exercise interventions for smoking cessation in people with mental illness: a systematic review and meta-analysis - Stefanie E. Schöttl; Martin Niedermeier; Prisca Kopp-Wilfling; Anika Frühauf; Carina S. Bichler; Monika Edlinger; Bernhard Holzner; Martin Kopp (BMC, 2022)
Abstract Background Smoking is the most common substance use disorder among people with mental illness. In contrast to people without mental illness, among whom the proportion of smokers has declined in recent decades, the proportion of smokers among people with mental illness remains high. There is a growing body of literature suggesting the use of exercise interventions in combination with smoking cessation in people without mental illness, but to our knowledge the available studies on this treatment option in people with mental illness have not been systematically reviewed. Therefore, this systematic review and meta-analysis aims to assess the effectiveness of exercise interventions as an adjunctive treatment for smoking cessation in people with mental illness. Methods Electronic databases (PubMed, Web of Science, PsycInfo, Sport Discus and Base) were searched for randomised controlled trials and prospective single-group studies that investigated exercise interventions in combination with smoking cessation programmes alone or in comparison with a control group in people with mental illness. A meta-analysis using the Mantel-Haenszel fixed-effect model was conducted to estimate the overall effect of treatment on smoking cessation (abstinence rate at the end of the intervention and at 6-month follow-up). Results Six studies, five randomised controlled trials and one study with a prospective single-group design, were included in the systematic review and four randomised controlled trials were included in the meta-analysis. The meta-analysis found a significantly higher abstinence rate after additional exercise at the end of the intervention [risk ratio (RR) 1.48, 95% confidence interval (CI) 1.13-1.94], but not at the 6-month follow-up (RR 1.34, 95% CI 0.89-2.04). Conclusions Exercise appears to be an effective adjunctive therapy to temporarily increase abstinence rates in individuals with mental illness at the end of the intervention. However, due to the small number of included studies and some risk of bias in the included studies, the results should be treated with caution. Therefore, future studies with larger samples are needed to provide a more accurate estimate of the effect in people with mental illness. Registration The systematic review and meta-analysis were registered in the International Prospective Register of Systematic Reviews (PROSPERO) (registration number: CRD42020178630).